Evaluasi Kegiatan Gerakan Tanam Sayur di Kecamatan Talang Kelapa Kabupaten Banyuasin - Agustina, Wely; Lisdiana, Lisdiana; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2023)
This Vegetable Planting Movement activity is one of the activities contained in the seven mainstay programs of Banyuasin Bangkit as stated in Banyuasin Regent Regulation Number 63 of 2019 concerning Strategic Plans for Regional Apparatuses in the Banyuasin Regency Government for 2018-2023, such as the creation of vegetable-producing areas and the aim of this vegetable planting movement is also to foster community participation in the utilization of home yards for family food security. By utilizing the land in the yard of the house in order to meet food needs (vegetables), the community can realize family food self-sufficiency and no longer need to buy vegetables because they are already available in the yard of the house. up to the next generation. The purpose of this study is to evaluate the activities of the Vegetable Planting Movement in Talang Kelapa District, Banyuasin Regency. The things that were identified were: Lack of outreach to the community about the importance of planting vegetables in the yard of the house, Participation of residents who were less active in responding to calls for activities to plant vegetables and Limited land for growing vegetables in the yard of the house. Evaluation of Vegetable Planting Movement Activities in Talang Kelapa District, Banyuasin Regency uses evaluation theory according to Stuffelbeam (2003: 78), namely as follows: 1) Context consists of objectives and benefits, 2) Input consists of: Human resources, funds or budget and goals, 3) Process consists of: Procedures for Vegetable Planting Movement Activities and Vegetable Planting Movement Activities, 4) Products consist of: Increased community economic welfare regarding food security and food self-sufficiency. This research shows that: overall the activities of the Vegetable Planting Movement in Talang Kelapa District, Banyuasin Regency have been carried out as they should, even though there are still obstacles in its implementation, namely the lack of outreach to the community about the importance of planting vegetables in the yard of the house, the participation of residents who are less active in responding calls for vegetable planting activities and limited land for growing vegetables in the yard of the house